Prenatal and childhood exposure to per- and polyfluoroalkyl substances (PFASs) and child cognition - Harris, Maria H.; Oken, Emily; Rifas-Shiman, Sheryl L.; Calafat, Antonia M.; Ye, Xiaoyun; Bellinger, David C.; Webster, Thomas F.; White, Roberta F.; Sagiv, Sharon K. (Environment international, 2018)
Per- and polyfluoroalkyl substances (PFASs) are suspected developmental toxicants, but epidemiological evidence on neurodevelopmental effects of PFAS exposure is inconsistent. We examined associations of prenatal and childhood PFAS exposure with performance on assessments of cognition in children. We included mother-child pairs from Project Viva, a longitudinal Boston-area birth cohort enrolled during 1999–2002. We quantified concentrations of eight PFASs, including perfluorooctane sulfonate (PFOS), perfluorooctanoate (PFOA), and perfluorohexane sulfonate (PFHxS), in plasma collected from women during pregnancy (median 9.7 weeks gestation) and from children at a visit in mid-childhood (median age 7.7 years). In early childhood (median age 3.2 years) we administered standardized assessments of visual motor skills and vocabulary comprehension, and in mid-childhood we assessed visual motor skills, visual memory, and verbal and non-verbal intelligence. Using multivariable regression, we estimated associations of prenatal and childhood PFAS plasma concentrations with children's cognitive assessment scores, adjusted for relevant covariates including breastfeeding, maternal intelligence, parental education, and household income. Samples sizes ranged from 631 to 971, depending on analysis. Prenatal PFAS concentrations were associated with both better and worse cognitive performance; children with top quartile prenatal concentrations of some PFASs had better visual motor abilities in early childhood and non-verbal IQ and visual memory in mid-childhood, while children with upper quartile prenatal PFOA and PFOS had lower mid-childhood visual-motor scores. In cross-sectional analyses of mid-childhood PFAS concentrations and cognitive assessments, visual-motor scores on the Wide Range Assessment of Visual Motor Abilities (WRAVMA) (standardized mean = 100, standard deviation = 15) were lower among children with higher PFHxS (fourth quartile (Q4) vs. Q1: −5.0, 95% confidence interval (CI): −9.1, −0.8). Upper quartiles of childhood PFOA and PFOS were also associated with somewhat lower childhood WRAVMA scores, but childhood PFASs were not associated with verbal or non-verbal IQ or visual memory. We present evidence suggesting associations of prenatal and childhood PFAS exposure with lower childhood visual motor abilities. Other results were inconsistent, with higher prenatal PFASs associated in some cases with better cognitive outcomes. •Per- and polyfluoroalkyl substances (PFASs) are suspected developmental toxicants.•We examined prenatal and childhood PFAS exposure in relation to child cognition.•Prenatal PFASs were associated with both better and worse cognitive scores.•Childhood PFASs were associated cross-sectionally with lower visual motor abilities.